DEVELOPMENT OF A SCIENCE E- MODULE BASED ON LOCAL PAPUAN WISDOM TO INCREASE STUDENTS' INTEREST AND LEARNING OUTCOMES IN THE 5TH GRADE HEAT TRANSFER MATERIAL - Marrung, Yakobus; Siregar, Tiurlina; Nainggolan, Jonner; Samosir, Hotlan; Nasri Lobo, Albertina (Jurnal Ilmu Pendidikan Indonesia, 2024)
This research aims to find out how to create, develop and feasibility of science e_modules in improving students’ abilities, interest and learning outcomes. The research method is research and development, the process used to develop and validate educational products carried out in class V of SD Negeri Inpres Perumnas IV Padang Bulan, with sample of 27 students. The research data collection instruments are egibility validator sheet for the lectures, science teacher response sheet, students response sheet, and pretest and postest question sheets. The research result show : 1) making a science e_ module with the stages of analyzing e_module needs, e_module design, and validating. 2) The feasibility of the science e_module developed optained a percentage of 94% with the category very suitable for use as a teaching material. 3) the science e_module is effective in improving students outcomes, obtaining n_gain  score which is 0,61 in the medium category.